Green skills - Francesco Vona; Giovanni Marin; Davide Consoli; David Popp (Fondazione Eni Enrico Mattei (FEEM), 2015)
While policymakers talk of "green skills", there is little systematic empirical research on the demand for skills that will be needed to operate and develop green technology. We propose a data-driven methodology to identify green skills and to gauge the ways in which the demand for these competences respond to environmental regulation. We find that green skills are high-level analytical and technical know-how related to the design, production, management and monitoring of technology. Environmental regulation triggers technological and organizational changes that increase the demand for these skills. Our analysis suggests also that this is not just a compositional change in skill demand due to job losses in sectors highly exposed to trade and regulation.
Keywords: J24; Q52; 330; Green Skills; Environmental Regulation; Task Model; Workforce Composition; Structural Shocks